Pola Penyebaran Konten Homoseksual Melalui Media Sosial Twitter - Gumelar, Rangga Galura; Kamila, Tasya (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
The emergence of new media contributes to the existence of people who are considered marginalized, social media, especially Twitter, provides space for gay groups to have fans or what is known as fujoshi. Fujoshi itself is a term for female fans who like Yaoi/Boy's Love manga.  Fujoshi in Indonesia consume and disseminate the content they find on social media and Twitter. The method used in this research is qualitative research that aims to explore information in depth and is open to various responses. In this method, researchers analyze opinions contained in various contents, such as text and images. Data collection techniques were interview, observation, literature study, and linguistic criticism. Research validation uses triangulation techniques and data analysis so that a conclusion can be made. The results of the study found that there is a pattern of spreading homosexual content on Twitter where the symbols expressed are not vulgar but fall into a unique category because there are text and image symbols about homosexuals. These symbols and terms are used to distinguish accounts that produce homosexual or gay content.